The Regulation Of Restrictions On Workers / Labourers Having Marriage In The Same Workplace - Riskiyanto Umar (Universitas Negeri Gorontalo, 2019)
The purpose of this study was to determine the regulation of restrictions on workers/laborers to marry in one office as regulated in the Decision of the Constitutional Court Number 13/PUU-XV/2017. The method used in this research is normative research and the type of approach used is the law approach, conceptual approach, and case approach. The technique of analyzing legal materials in this study uses a systematic interpretation method. The results of the study show that the provisions of Article 153 paragraph 1 letter f explain that employers are prohibited from terminating employment because the worker/ laborer has blood ties and/or marital ties with other workers/ laborers in the same company unless it has been stipulated in a work agreement, regulations company, or collective work agreement.